Media Pembelajaran PJOK Materi Teknik Dasar Sepak Bola Berbasis Aplikasi Articulate Storyline - Rika Navi'atul Khasanah (Universitas Syiah Kuala, 2022)
AbstractThe purpose of this research is to develop PJOK learning media in the form of interactive multimedia in the form of the Articulate Storyline application. So it is hoped that through the development of this learning media it can help and make it easier for PJOK teachers in high schools to convey basic soccer technical material in an interesting way and help students understand basic soccer technical material easily. This study uses development research methods with data obtained in the form of qualitative and quantitative data. The results showed that the average value obtained from the validation of soccer learning experts was 89%, the validation of learning media experts was 96.2%, the PJOK expert validation was 89.4%, the small group trial was 90.6% and the try a large group that is 90.8%. From this research, it can be concluded that the learning media for basic soccer technique material based on the Articulate Storyline application for class XI students of SMA Negeri 2 Batu is feasible to be applied without any revision.